Adolescents’ and parents’ perceptions of parental monitoring as predictors of academic functioning at the end of high school - Gagné-Legault, Guillaume; Cimon-Paquet, Catherine; Véronneau, Marie-Hélène (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2025)
This article examines how parents’ and adolescents’ perceptions of parental solicitation and control can be used to predict academic achievement and engagement. Hierarchical regressions on 133 parent-child dyads (66% girls; mean age: 16.88 years) indicate that adolescents’ perceptions of parental control are significantly related to their academic engagement and achievement, in contrast to perceived solicitation, which is only marginally related to engagement. Parents’ perceptions of their monitoring strategies, however, do not predict adolescents’ academic functioning. Thus, it would be important to consider adolescents’ perceptions of parental monitoring in interventions aimed at improving academic functioning in high school students.